2022
DOI: 10.1186/s13099-022-00517-w
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into zoonotic transmission and antimicrobial resistance in Campylobacter jejuni from farm to fork: a one health perspective

Abstract: Background Campylobacteriosis represents a global public health threat with various socio-economic impacts. Among different Campylobacter species, Campylobacter jejuni (C. jejuni) is considered to be the foremost Campylobacter species responsible for most of gastrointestinal-related infections. Although these species are reported to primarily inhabit birds, its high genetic and phenotypic diversity allowed their adaptation to other animal reservoirs and to the environment that may impact on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…In this study, genome analysis showed a significant genetic divergence in the selected collection. The assignment to different STs and CCs demonstrated that 41% of the C. jejuni strains were grouped into two main CCs, ST-21 CC and ST-206 CC, defined as host generalists (capable of infecting wide range of host species) ( Baumler and Fang, 2013 ; Thépault et al, 2017 ; Bravo et al, 2021 ; Mouftah et al, 2021 ; Dessouky et al, 2022 ; Ghielmetti et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, genome analysis showed a significant genetic divergence in the selected collection. The assignment to different STs and CCs demonstrated that 41% of the C. jejuni strains were grouped into two main CCs, ST-21 CC and ST-206 CC, defined as host generalists (capable of infecting wide range of host species) ( Baumler and Fang, 2013 ; Thépault et al, 2017 ; Bravo et al, 2021 ; Mouftah et al, 2021 ; Dessouky et al, 2022 ; Ghielmetti et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a generally high concordance between antibiotic resistance genotypes and phenotypes, tetracycline exhibited the lowest correlation between the presence of the tet gene and susceptibility patterns. The absence of complete matching is widely described worldwide due to a misdetection of some AMR mechanisms ( Engberg et al, 2001 ; Luo et al, 2003 ; Painset et al, 2020 ; Rokney et al, 2020 ; Mouftah et al, 2021 ; Dessouky et al, 2022 ). Without a precise mechanism, erythromycin and/or tetracycline resistance could be present due to mutations in CmeABC operon, its transcriptional regulator CmeR or in its promoter ( Aksomaitiene et al, 2018 ; García-Fernández et al, 2018 ; Oncel et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Directions for new research may be taken from the study of other generalist bacterial pathogens with multiple environmental reservoirs. For example, species of the genus Campylobacter similarly occupy a wide variety of environments and are a leading cause of food-borne illness (67). Studies combining epidemiological and sequencing data have proven very useful in identifying the animal and environmental sources of Campylobacter infection (68)(69)(70).…”
Section: The Problem Of Transmissionmentioning
confidence: 99%
“…C. jejuni gastroenteritis is a zoonotic disease: C. jejuni is transmitted to humans from animals, primarily chickens, where C. jejuni is part of normal intestinal microbiota, but can also be transmitted from cattle, pigs, sheep and, as the more recent evidence suggests, domestic cats and dogs [ 4 ]. C. jejuni infection in humans is typically acquired through contact with contaminated animal food products, most commonly poultry, as well as through contaminated water and milk [ 5 ].…”
Section: Introductionmentioning
confidence: 99%